Persistent And Concurrent Server For Reliable Transacton (International Journal of Engineering and Computer Science, 2017)
This paper provides Reliability that has to be implemented in the Client –Server communication ina network .The most important thing in client server communication is the reliability of data. In an onlinetransaction all the data is transferred over the network there are several factors like hardware crisis orunavailability of network which prevent the total reliability factor. For this purpose it is required that the datashould have a backup. Not only the data but the webserver can have these problem.Inorder to overcome theseproblems we merge the concept of mirroring of data with the help of a primary and secondary webserver. Eachwebserver runs independently on a different machine. The machine will have two NIC(NETWORK INTERFACECARD) cards. In the server1 the first NIC card will be configured to the static ip which will be accessed by theclient. In a point of failure the second NICin the primary server will be in communication with the first NICinthe server2. When the query from the First NIC in server2 fails it assigns the static ip to the second NICin theserver2. By this mechanism the client will have uninterrupted usage of the server even when the server2fails.Another key aspect of this project is that it will take regular backup of the data in the database server tothe secondary database server in which RAID 10 concept is used. This process will occur for a small interval oftime as decided by the user. This paper use the RSA Algorithm to provide the Security to the client data duringbackup